Participation and Objectivity. - Koskinen, Inkeri (Philosophy of Science, 2023)
Many philosophers of science have recently argued that extra-academic participation in scientific knowledge production does not threaten scientific objectivity. Quite the contrary: Citizen science, participatory projects, transdisciplinary research, and other similar endeavours can even increase the objectivity of the research conducted. Simultaneously, researchers working in fields in which such participation is common have expressed worries about various ways in which it can result in biases. In this article I clarify how these arguments and worries can be compared, and how extra-academic participation can both increase and threaten the objectivity of the research conducted.